2021
DOI: 10.1186/s12885-021-09079-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic scoring model for mortality risk stratification in patients with recurrent or metastatic gastric carcinoma

Abstract: Background Survival times differ among patients with advanced gastric carcinoma. A precise and universal prognostic evaluation strategy has not yet been established. The current study aimed to construct a prognostic scoring model for mortality risk stratification in patients with advanced gastric carcinoma. Methods Patients with advanced gastric carcinoma from two hospitals (development and validation cohort) were included. Cox proportional hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Here, this issue is addressed by repeating the holdout CV five times, so the performance is unbiased in the local cohort, as measured by AUROC, recall, and precision. All the AUROCs of the three models exceed 0.75, which is higher than those in the previous reports ( Koo et al, 2011 ; Custodio et al, 2017 ; Ma et al, 2021 ). In addition, our earlier work selected the patients with AGC receiving first-line chemotherapy from the same local cohort and compared the performances of seven survival prediction models on it, showing the best model having an AUROC of 0.60 ( Xu et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Here, this issue is addressed by repeating the holdout CV five times, so the performance is unbiased in the local cohort, as measured by AUROC, recall, and precision. All the AUROCs of the three models exceed 0.75, which is higher than those in the previous reports ( Koo et al, 2011 ; Custodio et al, 2017 ; Ma et al, 2021 ). In addition, our earlier work selected the patients with AGC receiving first-line chemotherapy from the same local cohort and compared the performances of seven survival prediction models on it, showing the best model having an AUROC of 0.60 ( Xu et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 66%
“…A Korean single-center study constructed a score-based model with an accuracy of 0.58 ( Koo et al, 2011 ), then externally validated another three models ( Chau et al, 2004 ; Lee et al, 2007 ; Kim et al, 2008 ), and showed similar performances in the same population ( Koo et al, 2011 ). Our previous work also developed a score-based model in a Chinese cohort with a c-index of 0.67 ( Ma et al, 2021 ). Meanwhile, we validated seven published models ( Chau et al, 2004 ; Lee et al, 2007 ; Kim et al, 2008 ; Koo et al, 2011 ; Takahari et al, 2014 ; Wang et al, 2016 ; Kim et al, 2020 ) in a Chinese population, and the results showed that the area under receiver operating characteristic (AUROC) curves was only about 0.60 ( Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not designed for patients initially diagnosed with metastatic GC, Ma et al built a nomogram model for mortality risk stratification in patients with advanced GC that included mucinous or non-mucinous histology, Eastern Cooperative Oncology Group score, bone metastasis, ascites, hemoglobin concentration, serum albumin level, lactate dehydrogenase level, carcinoembryonic antigen level, and chemotherapy treatment. 21 Hannah et al reported that the Viennese risk prediction score for Advanced Gastroesophageal carcinoma based on Alarm Symptoms could be used at the time of initial diagnosis of patients with metastatic gastro-esophageal cancer. The score system comprises five factors: stenosis in endoscopy, weight loss, HER2 positivity, dyspepsia, and ulcer or active bleeding; the model was applied not only to GC but also to esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis that included 14,651 patients, increased pretreatment serum CEA levels nearly doubled the risk of mortality in patients with gastric cancer. 52 In a study on 615 Chinese patients with advanced gastric cancer, a CEA level of ≥8 ng/mL was associated with higher death risk compared to that of <8 ng/mL, and therefore, CEA has been incorporated into a prognostic scoring model for mortality risk stratification. 53 However, because other studies have indicated otherwise, [54][55][56][57][58] CEA is not considered an independent predictor for patients with gastric cancer, and curative approach should not be tailored based on CEA level.…”
mentioning
confidence: 99%